ReneeReyes.com

Atlanta's Foremost Transgender Woman

menu

ReneeReyes.com

Atlanta's Foremost Transgender Woman



Arguments Against Sex Change Operation


Sex Change Failures



They "observed" the high number of trans women who ending up emotionally miserable following gender reassignment surgery. Based upon this observed event DR. XX proceeds to surmise transgenderism is just a mental health issue akin to anorexia - most "imagine" they're fat. Have you ever walked through a mall and had people call you vulgar names? Our self image isn't imaginary



The issue of if GRS resolves the issues of gender dysphoria associated with transsexualism is hotly debated.

One highly visible opponent is DR. XX who published position arguments against GRS as a solution. DR. XX most often quotes statistics from a prior study from XX and arrives at his own personal subsequent conclusions that iffy at best - and certainly not in concert with an individual that should be well versed in scientific study given that he's got a pHD behind his name. Alas, its in psychology - and that field is often built upon unsubstantiated conclusions from observation vs. hard facts.

The Key Argument Points of DR. XX

Intersex outcomes - 100% proof otherwise

Studying Success vs. Failure to Find Solutions

Failures are a source for lots of insights when seeking breakthrough solutions.

Edison proudly stated he discovered 10,000 ways not to create an incandescent light bulb during his research.

Failures aren't a good source for solutions

Financial advice from Buffett vs. XX

Its important not to ignore failures as if they don't exist






given

Sex Change Operation -



1 + 1 = 3

Show equation

One wrong supposition - and the entire edifice supporting science fails


Here are some so called proofs to prove “1 + 1 = 3”:
41 – 40 = 61 – 60
=>16 + 25 – 2*5*4 = 36 + 25 – 2*5*6
=>4^2 + 5^2 -2*5*4 = 6^2 + 5^2 – 2*5*6
Using the identity: a^2 + b^2 - 2ab = (a - b)^2
=>(4 - 5)^2 = (6 - 5)^2
Taking square root both the sides:
=>(4 - 5) = (6 - 5) **
=>4 = 6
Dividing by 2
=>2 = 3
=>1 + 1 = 3
Hence proved!
Alternate proof:
Start with the following equation:
Let a = b
Multiply both sides by b:
=>ab = b^2
Subtract a^2 from both sides and factorize:
=>ab − a^2 = b^2 − a^2
=>a (b−a) = (b+a) (b−a)
Simplify and add 1 to both sides:
=>a = b+ a**
=>a + 1 =b + a + 1
Now since a = b (the starting point of this proof), we can write this as:
=>a + 1 =2a + 1
And in the case where a = 1, we have:
=>1 + 1 = 2 + 1
=>1 + 1 = 3
Hence proved!
Note:
If you can’t figure out what’s wrong with the given proofs, look again the star marked equations.
In the first proof:
(4 - 5) = (6 - 5)
This statement implies -1 = 1 which is wrong!
In the second:
a (b−a) = (b+a) (b−a)
Simplify
=>a = b+ a
This statement may appear correct but for simplifying, the equation is divided by (b-a) which is 0.
Hence proved. You cannot use correct Maths to prove an incorrect statement.


outcomes

Takes a lot of money - like if you have a physical ailment
Need to safely & effectively morph hips and ass
Must pull away from trans life
Learn to
be a woman - from other women: not from transgender women.